Barriers to Entry and Profitability - Diana Heger; Kornelius Kraft (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Barriers to entry are regarded as major impediments to the working of markets. Entry must not necessarily actually take place - the perceived threat of entry may encourage incumbent firms to behave as if they are in a competitive market, even if they are not. We present empirical evidence on effects of perceived threat of entry on profitability. Using information from managers about how they assess the existence of entry barriers a strong impact of these assessments on profitability is confirmed. The number and the relative size of competitors also exert considerable effects. We find no statistically significant relation between the perceived threat of entry and the actual number of firms if the size of the relevant market is taken into account.
Keywords: C25; L25; L13; 330; Barriers to Entry; Profitability; Discrete Regression Models; Potenzieller Wettbewerb; Wahrnehmung; Markteintritt; Betriebliche Preispolitik; Rentabilität; Struktur-Performance-Modell; Marktstruktur; Fixkosten; Theorie; Schätzung; Verarbeitendes Gewerbe; Deutschland